The Principles of the Universe (Global Journal of Science Frontier Research, 2026)
This paper presents a unified framework—the Principles of Matter, Space, and Time—to explain the structure and behaviour of the universe through the concept of hierarchical unities. It proposes that all matter possesses mass and energy, organizing itself into nested unities through the interplay of potential-energy (Ep), sharing-energy (Es), and excess-energy (Ee). The paper introduces unity force (Fu = Es + Ee) as a generalization of inertia, encompassing both inertia-at-rest (as gravity or weight) through Es and inertia-in-motion (as motion or heat) through Ee. Within this framework, gravity emerges not as spacetime curvature but as matter’s active pull toward its unity centre, and matter moves only relative to its unity centre, eliminating the need for external reference frames and relativity. The paper further proposes that space and time are not physical entities but properties of matter: space is not preexisting but emerges from matter’s three-dimensional movements, eliminating the notion of vacuum, and time is a series of heat transfers rather than a physical dimension. Consequently, spacetime is only a mathematical construct without physical reality. The paper argues that these principles govern atomic structure, planetary motion, galactic organization, and black hole formation, that the universe comprises only matter and its movements in three dimensions, experiences heat transfers, resulting in its evolution and revolution
Keywords: energy; inertia; mass; matter; space; time; unity; unity force; universe.